1997
DOI: 10.1021/ma961705h
|View full text |Cite
|
Sign up to set email alerts
|

Chimeric Liquid Crystallinity:  Noncovalent Association of DNA and Bacterial Levan

Abstract: The liquid-crystalline phase of cell-free and nominally pure bacterial levan in water is shown to depend on the presence of DNA. The necessary concentrations of DNA are 2 orders of magnitude lower than those needed to stabilize a mesophase in aqueous solutions of DNA on its own and are similarly small in comparison to the number concentration of the globular levan molecules. A partial phase diagram for liquid crystallinity in the ternary system water/levan/DNA is mapped out. A model is proposed in which the le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…column was used to remove both DNA and RNA, with purity being monitored by a combination of absorbance measurements, agarose gel electrophoresis, fluorescent molecular probes, and dynamic light scattering [16,17]. TPLM and turbidimetry showed that aqueous solutions of the purified levan had lost the ability to develop liquid crystalline order.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…column was used to remove both DNA and RNA, with purity being monitored by a combination of absorbance measurements, agarose gel electrophoresis, fluorescent molecular probes, and dynamic light scattering [16,17]. TPLM and turbidimetry showed that aqueous solutions of the purified levan had lost the ability to develop liquid crystalline order.…”
mentioning
confidence: 99%
“…TPLM revealed a nematic liquid crystalline texture (of undetermined chirality), indistinguishable from that exhibited by solutions of as-received levan. Turbidity characterization enabled us to determine the ternary phase diagram for water/levan/ctDNA [16,17]. The concentra-tion of ctDNA needed to restore liquid crystallinity is 2 to 3 orders of magnitude smaller (by weight) than that of the levan.…”
mentioning
confidence: 99%
See 1 more Smart Citation